Teaching Vocabulary Through Songs Of Language Education At Al Asyariah Mandar University - Muthmainnah Muthmainnah (Fakultas Keguruan dan Ilmu Pendidikan Univ. Al Asyariah Mandar Sulbar, 2017)
This research was conducted to find out whether or not the use of songs improve the students’ vocabulary to the first semester students of language education at Al Asyariah Mandar University. The research was an experimental design with Gay et all., design. The researcher uses census system the population was the the first semester students, all of the population was taken as sample. The number of population were about 58 students spread in three classes namely class A and class B. The students was chosen as the sample of the research were 32 students at experiment class and 26 students at control class. This research conducted at language education to the first semester students of Al Asyariah Mandar University at West Sulawesi 2016 academic year. The data of the students’ achievement were collected by using pretest and posttest. The data obtained through the test were subjected to paired sample t test for dependent sample to see the significant difference in the pre-test and post-test. These data were then analyzed quantitatively using paired samples t-test to see the significance different for each aspects and all aspects in the pretest and posttest. The findings of the study indicated that the result of post-test was significantly higher than that of pre-test. This means that using songs in teaching English contributed to the students Vocabulary.